The controversial space of complex systems - Rodríguez Zoya, Leonardo G.; Rodríguez Zoya, Paula G. (Estudios de Filosofía, 2014)
The goal of this paper is to apply the model of controversial spaces, as developed by Oscar Nudler, to the philosophical and scientific fields connected with complexity. Our analysis relies on three approaches: the science of complexity, the constructivist theory of complex systems, and complex thought. The argumentative structure of the article is organized in three parts. First, we develop a conceptual introduction to the model of controversial spaces; second, we analyze the controversial space of complex systems; finally, we present our conclusions.